Appreciative Inquiry: An Experiential Exercise and Course Feedback Tool. (June 2017) - Scandura, Terri A.
The action research method of appreciative inquiry (AI) was employed to develop a teaching tool. This exercise involves students' reflections on a course, noting when they learned the most. The AI process of appreciating, envisioning, dialoging, and innovating is used to help students reflect on how they learn. Instructors of all types of courses at both the undergraduate and master's degree levels gain understanding of student learning and ideas on how to improve courses. The exercise and sample responses from students are provided to demonstrate how the exercise works. Three variations are presented: mapping the exercise onto Kolb's learning styles, running the exercise at the midpoint of a course, and a case study of an AI implementation in an organization.